Conversion of Intercalated MoO3 to Multi‐Heteroatoms‐Doped MoS2 with High Hydrogen Evolution Activity. Issue 30 (22nd June 2020) - Yang, Weiwei; Zhang, Shuqing; Chen, Qian; Zhang, Chao; Wei, Yi; Jiang, Huaning; Lin, Yunxiang; Zhao, Mengting; He, Qianqian; Wang, Xingguo; Du, Yi; Song, Li; et al.
Abstract: Lack of effective strategies to regulate the internal activity of MoS2 limits its practical application for hydrogen evolution reactions (HERs). Doping of heteroatoms without forming aggregation or an edge enrichment is still challenging, and its effect on the HER needs to be further explored. Herein, a two‐step method is developed to obtain multi‐metal‐doped H‐MoS2, which includes intercalation of the layered MoO3 precursor with a following sulfurization. Benefiting from the capability of the intercalation method to uniformly and simultaneously introduce different elements into the van der Waals gap, this method is universal to obtain multi‐heteroatoms co‐doped MoS2 without forming clusters, phase separation, and an edge enrichment. It is demonstrated that the doping of adjacent cobalt and palladium monomers on MoS2 greatly enhances the HER catalytic activity. The overpotential at 10 mA cm −2 and Tafel slope of Co and Pd co‐doped MoS2 is found to be 49.3 mV and 43.2 mV dec −1, respectively, representing a superior acidic HER catalytic activity. This intercalation‐assisted method also provides a new and general strategy to synthesize uniformly doped transition metal dichalcogenides for various applications. Abstract : An intercalation‐assisted method is developed to obtain multi‐metal‐doped H‐MoS2, which is proven to be a universal method. The doping of adjacent cobalt and palladium monomers on MoS2 greatly enhances the HER catalytic activity. The overpotential at 10 mA cm −1 and Tafel slope of Co‐Pd‐MoS2 are 49.3 mV and 43.2 mV dec −1, respectively.